2011
DOI: 10.1007/s13157-011-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of Soil Properties and Nitrogen Cycling in Created Wetlands

Abstract: Mitigation wetlands are expected to compensate for the loss of structure and function of natural wetlands within 5-10 years of creation; however, the age-based trajectory of development in wetlands is unclear. This study investigates the development of coupled structural (soil properties) and functional (nitrogen cycling) attributes of created non-tidal freshwater wetlands of varying ages and natural reference wetlands to determine if created wetlands attain the water quality ecosystem service of nitrogen (N) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 61 publications
(97 reference statements)
2
25
0
Order By: Relevance
“…These results support those of Richardson et al (2004), who found that denitrification rates significantly increase with the addition of NO 3 − to floodplain wetlands. Study results also support similar studies where denitrification was positively correlated with redox potential (Verhoeven et al, 2001) and soil moisture (Schnabel et al, 1997; Hunter and Faulkner, 2001; Groffman and Crawford, 2003; Wolf et al, 2011a,b). …”
Section: Discussionsupporting
confidence: 89%
“…These results support those of Richardson et al (2004), who found that denitrification rates significantly increase with the addition of NO 3 − to floodplain wetlands. Study results also support similar studies where denitrification was positively correlated with redox potential (Verhoeven et al, 2001) and soil moisture (Schnabel et al, 1997; Hunter and Faulkner, 2001; Groffman and Crawford, 2003; Wolf et al, 2011a,b). …”
Section: Discussionsupporting
confidence: 89%
“…Soil organic matter comprises decomposed and decomposing plant and animal materials, which give high‐organic matter soils their characteristically high levels of SOC and N. Although natural wetland soils are abundant in SOC and N, this is generally not the case in newly restored wetlands, where total organic C and total N tend to increase with age (Wolf et al ). The significant correlations between denitrification potential, SOC, and microbial biomass N observed across sites suggest that the microbial communities performing denitrification are C‐limited in these restored wetlands, such that higher concentrations of SOC support larger microbial communities and thereby enable more denitrification potential.…”
Section: Discussionmentioning
confidence: 99%
“…in the process of wetland evolution and recovery (Zheng et al 2011;Wolf et al 2011). The conditions of change in soil texture are difficult to isolate due to the influence of flooding in wetlands (Wang et al 2005;Hossler and Bouchard 2010).…”
Section: The Effect Of the Reverse Seasonal Flooding On Soil Texturementioning
confidence: 99%